The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/ajhb.1084
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal function in context: Biocultural observations on Amish, neighboring non‐Amish, and Ifugao household health

Abstract: Ecological approaches to female post-reproductive function must consider the social context and microenvironment of the household. A model integrating these environmental factors into the analysis of late-life well-being (operationally defined as household health) is presented and explored in three settings: an Old Order Amish community, the neighboring community of non-Amish, and an Ifugao community in the Philippine highlands. Intensive interview and observation of function were completed in a sample of at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Because midlife is a multifaceted transitional stage in women's development (Palacios et al, 2002; Short, 2003; Rosenberger, 1993; Stotland, 2002; Woods & Mitchell, 1999), understanding of cultural contextual factors that may influence the menopausal symptom experience is essential (Carolan, 2000; Deeks, 2003; Hewner, 2001). Menopause occurs at a time of life when women are facing many threats and challenges (e.g., children leaving home, the illness of their partner, or the death of elderly parents), and cultural perspectives of these challenges vary depending on ethnic-specific cultural contexts (Woods & Mitchell, 1999).…”
mentioning
confidence: 99%
“…Because midlife is a multifaceted transitional stage in women's development (Palacios et al, 2002; Short, 2003; Rosenberger, 1993; Stotland, 2002; Woods & Mitchell, 1999), understanding of cultural contextual factors that may influence the menopausal symptom experience is essential (Carolan, 2000; Deeks, 2003; Hewner, 2001). Menopause occurs at a time of life when women are facing many threats and challenges (e.g., children leaving home, the illness of their partner, or the death of elderly parents), and cultural perspectives of these challenges vary depending on ethnic-specific cultural contexts (Woods & Mitchell, 1999).…”
mentioning
confidence: 99%
“…A plausible reason for this finding could be: psychological and menstrual symptoms tend to be closely linked to cultural attitudes toward menstruation and menopause. Indeed, researchers have suggested that any understanding of menopause should be placed within the context of a woman’s life and should include a consideration of her psychological state, psychological influences, cultural and social background, social contexts, the microenvironment of the household, and the aging process (Avis, et al, 2005; Deeks, 2003; Hewner, 2001; Obermeyer, Reher, & Saliba, 2007; Sievert, Obermeyer, & Saliba, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The settlement structure protects members against external assimilating forces (Hostetler 1955) and is necessary to re-create their characteristically stable, dense networks (Hewner 2001;Savells 1988). Therein, members are embedded in ever-wider social circles: family, extended family, the immediate church district, peers, settlement (multiple church districts in one location), schoolmates, and so forth.…”
Section: Background Theorizing Amish Migration and Community Reestablmentioning
confidence: 99%
“…With a 20.5-year doubling time-a window that narrowed across the twentieth century-the approximately 251,000 Amish adherents residing in 472 settlements (as of 2013) are on track to number 1 million among 1,000 settlements shortly after 2050 (Donnermeyer 2015;Donnermeyer, Anderson, and Cooksey 2013;Donnermeyer and Luthy 2013). Over half of the population consists of adolescents and children (Cross and McKusick 1970;Hewner 1998;Hostetler 1993Hostetler [1963; Smith 1960). High fertility (Ericksen et al 1979;Greksa 2002) and an ever-increasing retention rate ranging from 80 percent to 95 percent (Hurst and McConnell 2010) account for this growth.…”
Section: Introductionmentioning
confidence: 99%